2006
DOI: 10.1152/ajplung.00281.2005
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intrauterine pulmonary hypertension selectively modifies pulmonary artery smooth muscle cell gene expression

Abstract: . Chronic intrauterine pulmonary hypertension selectively modifies pulmonary artery smooth muscle cell gene expression. Am J Physiol Lung Cell Mol Physiol 290: L426 -L432, 2006; doi:10.1152/ajplung.00281.2005.-Pulmonary artery smooth muscle cell (PASMC) relaxation at birth results from an increase in cytosolic cGMP, cGMP-dependent and kinase-mediated activation of the Ca 2ϩ -sensitive K ϩ channel (KCa), and closure of voltage-operated Ca 2ϩ channels (VOCC). How chronic intrauterine pulmonary hypertension comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 50 publications
3
24
0
Order By: Relevance
“…We isolated fifth-generation pulmonary artery SMCs from control and PPHN lambs and confirmed that the PPHN cells maintained their phenotype in culture by demonstrating a decrease in expression of PKG-1a (data not shown), in agreement with the previous study of Resnik et al (35). We then exposed the cells to 95% O 2 for 24 h to mimic the effects of hyperoxia on lambs ventilated with 100% O 2 .…”
Section: Pphn and Hyperoxia Increase Ecsod Expression But Decrease Acsupporting
confidence: 87%
“…We isolated fifth-generation pulmonary artery SMCs from control and PPHN lambs and confirmed that the PPHN cells maintained their phenotype in culture by demonstrating a decrease in expression of PKG-1a (data not shown), in agreement with the previous study of Resnik et al (35). We then exposed the cells to 95% O 2 for 24 h to mimic the effects of hyperoxia on lambs ventilated with 100% O 2 .…”
Section: Pphn and Hyperoxia Increase Ecsod Expression But Decrease Acsupporting
confidence: 87%
“…The techniques used for the isolation of ovine PA SMC have been described (27). Distal PAs were quickly excised from pentobarbital-anesthetized ovine fetuses and placed in physiological saline solution (120 mM NaCl/5.9 mM KCl/11.5 mM dextrose/25 mM NaHCO 3 /1.2 mM NaH 2 PO 4 /1.…”
Section: Methodsmentioning
confidence: 99%
“…The dispersed cell suspension was aliquoted onto 25-mm 2 glass coverslips coated with poly-L-lysine (Sigma) and into 25-cm 2 tissue culture flasks (Falcon Plastics, Oxnard, CA) at a density of 5 Ϫ10 ϫ 10 3 cells/cm 2 . The cells were incubated at 37°C in either a humidified 5% oxygen, 5% CO 2 balance nitrogen atmosphere or a humidified air, 5% CO 2 atmosphere (27,28). After 18-24 h the cultures were washed once with Hanks' balanced salt solution to remove nonadherent cells and debris and refed with fresh medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PKG expression and/or activity are/is reduced in animal models of pulmonary arterial hypertension (PAH) induced by ligation of the ductus arteriosus of fetal lambs (Resnik et al, 2006) and in caveolin-1 (Cav-1) knockout mice (Zhao et al, 2009). Cav-1, a 21-kDa integral membrane protein, is an intracellular physiological inhibitor of eNOS activity.…”
Section: Pulmonary Arterial Hypertensionmentioning
confidence: 99%